Analysis of the Causes of Sensitive Teeth in the Community of Nibong Village, North Aceh District - Salfiyadi, Teuku; Muliati, Cut Sirri; Reca, Reca; Aja Nuraski, Cut; Halimatussakdiah, Halimatussakdiah (Jurnal Kesehatan Gigi, 2025)
Sensitive teeth are a general term to denote hypersensitive dentine, which is a painful sensation that occurs in the exposed dentin/root of the tooth due to external stimuli such as heat, cold, and acid, especially in areas where the periodontal lining is missing. Hypersensitive dentin is correlated with abrasion when brushing teeth, periodontal disease, erosion from food or acid, and possibly increased scaling and gum recession. The results of the examination of the community in Nibong Village, North Aceh District, in early 2025 showed that out of 84 samples, 36 people were found to have sensitive teeth. The purpose of this study was to determine the factors that cause tooth sensitivity in the community. This type of research is a case study by conducting descriptive analysis. This study shows 36 people; there are 9 people who have  periodontal disease status  who are still healthy,  besides  experiencing complaints  of aching  or sensitive teeth as many as 30 people, there are shallow pockets (80.6%), assessment based on the division of the square of only 12 healthy conditions, the rest 82 have periodontal disease. In the examination of gingival recession of 21 people (53.3%), some thinning of the tooth enamel layer, gingival recession of 21 people (58.3%), thinning enamel conditions, and as many as 24 people (66.7%) are at risk of gingival recession. It can be concluded that the main cause of tooth sensitivity in the community is the habit of applying excessive pressure when weeding.